IMPROVING SELF-MANAGEMENT FOR POST STROKE PATIENTS THROUGH STROKE EMPOWERMENT EDUCATION AS PREVENTION OF RECURRENT STROKE AT RSUD GAMBIRAN KEDIRI CITY - Christina Dewi Prasetyowati; Giovanni Iga Firmanda (Jurnal SMART Keperawatan, 2025)
Introduction : Stroke can result in a wide range of outcomes, including recovery with disabilities, death or survival with the risk of reccurent strokes. Post-stoke patients require special attention to improve self-management behaviors. Stroke empowerment education is an educational approach given to stroke patients with an empowerment focus that centers on the patient. Objective : This study aimed to determine the impact of stroke empowerment education on the self-management of post-stroke patients as a strategy to prevent recurrent strokes at RSUD Gambiran Kota Kediri. Methods : The research design used was a Quasi-Experiment with a pre-post test design with a control group. The sampling method used was accidental sampling technique, resulting in 98 respondents. Self-management data were gathered through the The Southampton stroke self-management questionnaire (SSSMQ). Results : The results of the Wilcoxon Signed Ranks Test showed a p-value of 0.000, meaning p < 0.05, thus rejecting H0. Conclusion : This study concluded that stroke empowerment education had a positive impact on enhancing self-management in post-stroke patients as a preventive measure against recurrent strokes at RSUD Gambiran Kota Kediri.